2019
DOI: 10.1186/s12891-019-2698-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of joint replacement surgery in Taiwanese female adults with systemic lupus erythematosus: a population-based cohort study

Abstract: Background Female patients with systemic lupus erythematosus (SLE) are prone to have musculoskeletal system involvement, which could lead to joint damage. However, few studies have assessed the incidence of arthroplasty in female patients with SLE. The aim of this study was to investigate the risk of total hip replacement surgery and total knee replacement surgery in patients with SLE. Methods We identified 577 female patients with newly diagnosed SLE between 2000 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
(24 reference statements)
0
10
1
2
Order By: Relevance
“…Demographics and clinical outcomes were summarized in Tables 1 Tables 2. Among the ten screened citations, seven were the case-control studies [7,11,14,15,17,23,24], two were retrospective [18,25], and one was cohort studies a study [10]. A total of 29573 hips in the SLE group were studied compared to 4013027 hips in the non-SLE group.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographics and clinical outcomes were summarized in Tables 1 Tables 2. Among the ten screened citations, seven were the case-control studies [7,11,14,15,17,23,24], two were retrospective [18,25], and one was cohort studies a study [10]. A total of 29573 hips in the SLE group were studied compared to 4013027 hips in the non-SLE group.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Periprosthetic fracture. Four studies [7,15,17,24]reported periprosthetic fracture on events following THA. After the heterogeneity test (OR 4.50,95% CI 0.43 to 46.97, I 2 = 98% > 50%, P < 0.1), it shows that the heterogeneity between the documents selected in this study is statistically signi cant, so we chose a random effect model, and it is necessary to nd the heterogeneity.…”
Section: Complicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen и соавт. [63], у пациенток с СКВ потребность в ТЭТБС была выше, чем у лиц без СКВ (p<0,001), особенно у лиц молодого возраста (p=0,001). Следует подчеркнуть, что в последние годы основным показанием к ТЭТБС у пациентов с СКВ стано-вится не ОН, а остеоартрит (ОА) [64,65].…”
Section: Hip Arthroplasty In Patients With Systemic Lupus Erythematosusunclassified
“…It can cause joint damage leading to deformity, and may require surgery to alleviate pain and restore function (4). Our previous studies have shown that patients with rheumatic diseases, such as rheumatoid arthritis, ankylosing spondylitis, and systemic lupus erythematosus, have increased risk of receiving total knee replacement (TKR) surgery or total hip replacement (THR) surgery (5)(6)(7). We speculated that psoriasis could also attack the joints of the knees and hips resulting in their destruction, which then lead to an increased risk of receiving TKR and THR.…”
Section: Introductionmentioning
confidence: 99%